A Comparative Jurisprudential Study of Sharia Alternatives to Usury in Earning Profit - نوري, د. نياز نوري أحمد (Sulaimani Journal for Humanities, 2025)
Forbidden usury is a small part of modern transactions and sales. It has no control over permitted sales. The basic principle regarding sales is that they are generally permissible, except for what is forbidden by a clear, definitive text. On this basis, we say: If usury does not exist in sales, banking, and banking, this does not mean that the rush of buying and selling will stop, but on the contrary, it will increase and grow. If there are sellers or banks whose dealings are unstable and whose profits are achieved only through usurious interest, as it seems to some, then there are alternatives and practical scientific solutions to the process of profit and the idea of developing and increasing money through legitimate means. In ways that are far from greed and exploitation of others. This is the main focus of our research, by explaining the legal alternatives to usury in banks, markets, and daily transactions in collecting profit and keeping pace with the market.
Keywords: Legitimate alternatives; usury; profit; banks; uncertainty